Web Scraping Analysis of Job Platform Adoption in Banten's Manufacturing Sector - Wijaya, Ferdian Bangkit; Budiaji, Weksi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study addresses the critical disconnect between Indonesia's manufacturing sector and the digitally native Gen Z workforce, focusing on Banten Province, a region with high youth unemployment despite its industrial concentration. We quantitatively assess the digital presence of manufacturing companies on key recruitment platforms, including LinkedIn, Jobstreet, and the government's Karirhub portal, to quantify this gap. Using web scraping techniques with Python, company profile data was systematically collected and analyzed. The findings reveal a limited digital footprint, with overall company presence recorded at 43.24% on LinkedIn, 42.70% on Karirhub, and a notably lower 32.97% on Jobstreet. Significant disparities exist across subsectors; consumer-facing industries like Food, Beverage, and Automotive show high digital engagement, while sectors such as Textiles, Electronics, and Non-metallic Minerals lag considerably. Notably, the Tobacco industry was found exclusively on the government's Karirhub platform. This confirmed digital divide hinders effective talent acquisition and limits job seekers' access to credible information. We conclude that a strategic imperative exists for manufacturers to enhance their digital recruitment strategies. This is crucial not only for attracting Gen Z talent but also for aligning with Indonesia’s national digitalization agenda to reduce unemployment.